2010
DOI: 10.1542/peds.2010-2006
|View full text |Cite
|
Sign up to set email alerts
|

Child Fatality Review

Abstract: Injury remains the leading cause of pediatric mortality and requires public health approaches to reduce preventable deaths. Child fatality review teams, first established to review suspicious child deaths involving abuse or neglect, have expanded toward a public health model of prevention of child fatality through systematic review of child deaths from birth through adolescence. Approximately half of all states report reviewing child deaths from all causes, and the process of fatality review has identified eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…This is consistent with prior work that assessed the CFR experience nationally12 and current AAP policy 8. Recent evidence shows that inconsistencies may exist across CFR programmes in policies, procedures and data acquisition 7.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with prior work that assessed the CFR experience nationally12 and current AAP policy 8. Recent evidence shows that inconsistencies may exist across CFR programmes in policies, procedures and data acquisition 7.…”
Section: Discussionsupporting
confidence: 87%
“…Since 1978, CFR teams have been established in the USA6 and currently, 48 states and the District of Columbia have active CFR programmes7 with more than 1000 review teams worldwide 4. A recent policy statement from the American Academy of Pediatrics emphasised the importance of CFR to influence local, state and national policies and reduce preventable fatalities 8. Similar statements have recently been published by child advocate authorities in Ireland9 and the UK 10…”
Section: Introductionmentioning
confidence: 90%
“…[10] The efficacy of CDR teams is the result of its multidisciplinary nature, consisting of a forensic pathologist, investigating officer, child protection worker (social worker), prosecutor and paediatrician as the core team who meet regularly to share case-specific information on the circumstances surrounding each child death. [11] Over the last three decades, CDR processes have evolved in high-income countries, with variation across countries, but most have adopted a prospective rapid response approach for all unexpected child deaths to understand the clinical causes and contributing factors. [10] Based on gaps identified by the child homicide study and a review of international practices to manage child deaths, a CDR process was identified as best practice for strengthening responses.…”
Section: Cmementioning
confidence: 99%
“…The kind of professionals who participate in the team differs among the countries where CDR is implemented (Fraser et al 2014). The CDR objectives are to (1) improve the quality of the procedure with regard to the determination of the cause of death as well as the death statistics, (2) identify avoidable factors that give directions for prevention, (3) translate the results into possible interventions and (4) support the family (Covington et al 2005; Cristian and Sege 2010; Ornstein et al 2013; Sidebotham and Pearson 2009). Each country using the CDR has a different review process (Vincent 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Each country using the CDR has a different review process (Vincent 2014). However, all countries share the four objectives of CDR, which is considered to be the gold standard in the management of child deaths by the American Academy of Pediatrics (Cristian and Sege 2010). …”
Section: Introductionmentioning
confidence: 99%